PAPYRACEOUS MUMMIFICATION LEADING TO DYSTOCIA OF A NORMAL FETUS IN A MECHERI EWE - ALAGAR, S; PRAKASH, S; SELVARAJU, M; RAVIKUMAR, K; MANOKARAN, S (The Indian Journal of Animal Reproduction, 2016)
Dystocia was diagnosed due to mummification of one of the twin fetuses in a Mecheri ewe. However, both the fetuses were delivered per-vaginally and the ewe recovered uneventfully.